Memulai Bisnis Itu Mudah Melalui Digital - Amir, Irham (Tazkia Islamic University College, 2024)
This training activity is motivated by the recognition that the involvement of youth is crucial for competitiveness on both national and international levels. Therefore, there is a need for attractive programs that can develop the potential of young people, such as digital marketing training. In fact, many Indonesian nationals studying in Saudi Arabia are not yet familiar with the latest concepts of digital marketing, thus unable to maximize business potential. Based on this motivation, the Digital Marketing Export training aims to: (i) Enhance digital marketing skills for young generations; (ii) Create quality and creative human resources as a foundation for entrepreneurship; (iii) Build business networks and foster young exporters. For participants, this activity is expected to broaden their insights in maximizing digital marketing for developing start-up businesses. For IAI Tazkia, this activity is anticipated to enhance its branding in entrepreneurship and digital marketing knowledge with Islamic values. It is also hoped that this activity will strengthen the collaboration between IAI Tazkia and the Indonesian Student Association (PPMI) in Saudi Arabia in developing digitally-based entrepreneurship potentials. Through this collaboration, it is also expected to introduce IAI Tazkia widely to Indonesian nationals in Saudi Arabia, consequently enhancing IAI Tazkia's image in Saudi Arabia. For business practitioners, this activity is expected to improve their understanding of initiating and developing businesses using appropriate business model prototypes and marketing tools, thus fostering young entrepreneurs who can effectively utilize digital technology.